Political Skills and Perceived Employability: Exploring the Mediating Role of Career Self-efficacy - Razaque, Tasneem; Pahi, Munawar Hussain; Aziz, Atif (Pakistan Journal of Humanities and Social Sciences, 2023)
This research study aims to explore the impact of political skills on perceived employability, focusing on the mediating effect of career self-efficacy among faculty of higher education institutes in Pakistan. By examining the employability issues faced by faculty in Pakistan’s higher education institutes, this study shed light on the challenges and opportunities for professional development in this domain. The survey was conducted using an administered questionnaire. A sample of N= 340 was selected through convenience sampling technique, ensuring representation from various higher education institutes of Pakistan. Data was collected from respondents through online Google forms. The questionnaires determine three variables: perceived employability, career self-efficacy, and political skills. The results indicated that career self-efficacy has a mediating role between political skills and perceived employability. Regression analysis also confirmed that political skills are positively correlated with perceived employability. Faculty members in higher education institutions should prioritize Self-managed career behaviors, such as developing career goals and implementing career tactics, as a means of enhancing their employability. In addition, management should launch formal and informal training programs for employees to strengthen feeling of success and career development. Providing employees with sufficient support and resources can help them improve their career self-efficacy and ensure their future employability.